Respuesta :

solve by completing the square
use formula (b/2 to the power of 2) in order to create a ner term. Solve for x by using this term to complete the square. 
x + -1 + i
          -

Answer:

0.586 or -3.414

Step-by-step explanation:

X² + 2X = -2

we make the equation 0

  • X² + 2X + 2 = 0  

The quickest way to solve a quadratic equation , is to use the almighty formular

which is

  • -b±√(b²- 4ac)/2a

where the coefficient of the first term starting from the Left Hand Side (LHS) is outlined as such

aX² + bX - C = 0

using our question,

X² + 2X + 2 = 0

a = 1 (coefficient of X² = 1)

b = 2 (coefficient of X = 2)

c = 2.

  • let's impute these values into our equation

x= -(2)±√(2² - 4(1×2))/2(1) =

x =-2±√(4-8)/2=

x = -2±√-4/2 = -2±√-2

i.e the root of our equation could be

x =-2+√2 or x = -2-√2

√2 = 1.414

∴ x = -2 + 1.414 = 0.586 or

  x = -2 - 1.414 = -3.414

ACCESS MORE